2021
DOI: 10.3390/ijerph18041727
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Depression on the Relationship between Social Support, Spirituality and Burnout in Family Members of Patients with Cancer

Abstract: When the treatment process of cancer patients changes to outpatient treatment, the burden on family members increases and they often experience burnout. Burnout not only effects the family members themselves but may also have a negative effect on the health of the cancer patient. Therefore, healthcare providers should evaluate burnout in the family members of cancer patients and actively make efforts towards their burnout management. This study investigated the mediating effect of depression on the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The study aims to clarify the correlation between care burden and depressive symptoms by using the Kumpfer's resilience model. First, the mean score of depressive symptoms was 22.33 ± 9.85, which was higher than that reported in previous studies using the same tool for caregivers of patients with other diseases, including dementia (40) and cancer (41). The difference can be attributed to stroke-related disabilities and long disease duration (42), which poses a heavy burden on caregivers of stroke patients.…”
Section: Discussionmentioning
confidence: 66%
“…The study aims to clarify the correlation between care burden and depressive symptoms by using the Kumpfer's resilience model. First, the mean score of depressive symptoms was 22.33 ± 9.85, which was higher than that reported in previous studies using the same tool for caregivers of patients with other diseases, including dementia (40) and cancer (41). The difference can be attributed to stroke-related disabilities and long disease duration (42), which poses a heavy burden on caregivers of stroke patients.…”
Section: Discussionmentioning
confidence: 66%
“…As indicated previously, gay men are more likely to be single and live alone which has also been found to affect access to care and caregiving relationships during cancer treatment (40). Although caregiver stress and burnout are recognized as a common complication of treating the chronically or terminally ill (41), caregivers of the SGM community face additional concerns. Studies find that caregivers of SGM patients tend to be younger, racially/ethnically diverse, more likely to have lower incomes, and less likely to be married (21).…”
Section: Introductionmentioning
confidence: 93%
“…30 ​When caregivers have strong self-efficacy, they are more capable of overcoming a variety of difficulties and psychological strains, quickly adjusting their emotions, and taking the initiative to use social resources to provide their patients the best care possible. 31 ​Previous study have found a positive correlation between caregiver self-efficacy and QoL: 32 ​cancer caregivers with higher self-efficacy can better perform their caregiving tasks and provide higher-quality care, improving patients' QoL. 30 ​Multiple intervention studies have shown that improving the self-efficacy of spouse caregivers significantly improves their physical and psychological health outcomes.…”
Section: Introductionmentioning
confidence: 98%